Strategi Asosiasi Petani Sawit Swadaya Amanah Dalam Pengelolaan Kelapa Sawit Berkelanjutan di Kecamatan Ukui - Agus Rinaldi; Dadang Mashur (Jurnal Ilmiah Wahana Pendidikan, 2022)
Asosiasi Petani Sawit Swadaya Amanah is a group of independent oil palm farmers in Pelalawan District, Ukui District. There is a negative issue regarding the environment that palm oil management results in deforestation. Farmers find it difficult to buy fertilizer and the garden has entered a period of oil palm rejuvenation. The purpose of this research is to know the association's strategy in sustainable palm oil management. The study uses the theory of organizational strategy from Stephen P. Robbins & Tymothy A. Judge (2013: 496). qualitative research method with a descriptive approach. Research results: The strategy of the Asosiasi Petani Sawit Swadaya Amanah in oil palm management has implemented aspects of oil palm plantation management following sustainable standards. The association innovated on deferring fertilizer funds and saving for replanting preparations. The association is supported by PT. Inti Indosawit Subur for training on palm oil management and market access. With the readiness of organizations and partnerships, providing support for the Amanah Association for sustainable palm oil certification.